IMPROVING STUDENTS’ SPEAKING SKILL THROUGH THREE-STEP INTERVIEW TECHNIQUE - Milasari Milasari; Endang Susilawati; Wardah Wardah (Universitas Tanjungpura, 2021)
AbstractThis research aimed to improve students’ speaking skill through three step interview technique in describing place for the tenth grade student at SMA Takhassus Al-Qur’an Ngabang in academic year 2020/2021. The research was conducted based on the problem found in teaching and learning process. Students had problem with pronunciation, grammar ( simple present tense ), vocabulary in speaking. The research was conducted through a Classroom Action Research in two cycles. The participats of this research were 14 students in class MIPA A. The research used observation checklist, field note and speaking performance test to collect the data of the research. The result showed that students could deliver the description with good pronunciation, correct grammar ( simple present tense ) and appropriate vocabulary. Based on the data, the students become more active in the teaching and learning activity. Modelling Three-Step Interview technique by asking questions in step 1 as interviewer, reversal role in step 2 and sharing idea as a teammate in step 3 the students help each other how to pronounce words, correcting the wrong grammar and choosing the appropriate vocabulary. As a result, the students are able to describe places with good pronunciation, correct grammar and proper vocabulary.Keyword : Speaking Skill, Three-Step Interview, Descriptive Text.